2002
DOI: 10.1001/jama.287.24.3215
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin for Prevention of Cardiac Events Following Successful First Percutaneous Coronary Intervention<SUBTITLE>A Randomized Controlled Trial</SUBTITLE>

Abstract: Fluvastatin treatment in patients with average cholesterol levels undergoing their first successful PCI significantly reduces the risk of major adverse cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 645 publications
(151 citation statements)
references
References 24 publications
4
131
0
5
Order By: Relevance
“…However, most studies that have supported a “lower is better” linear relationship between LDL cholesterol and outcomes have been conducted in younger populations. Indeed, elderly populations have been significantly under‐represented in statin and PCSK‐9 inhibitor outcome trials 5, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35. Our study suggests that the linear “dose‐dependent” relationship between LDL cholesterol and outcomes may not apply to elderly populations on statins following ACS hospitalizations, and the effectiveness of using aggressive LDL cholesterol targets among such elderly subpopulations may be unwarranted.…”
Section: Discussionmentioning
confidence: 90%
“…However, most studies that have supported a “lower is better” linear relationship between LDL cholesterol and outcomes have been conducted in younger populations. Indeed, elderly populations have been significantly under‐represented in statin and PCSK‐9 inhibitor outcome trials 5, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35. Our study suggests that the linear “dose‐dependent” relationship between LDL cholesterol and outcomes may not apply to elderly populations on statins following ACS hospitalizations, and the effectiveness of using aggressive LDL cholesterol targets among such elderly subpopulations may be unwarranted.…”
Section: Discussionmentioning
confidence: 90%
“…Randomized trials considered for this analysis are listed in table 1[11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. After screening for eligibility we selected 29 trials accounting for a total of 90,480 patients, with a mean age of 59 years and a mean follow-up of 3.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21] [22] These drugs, especially Fluvastatin, are prescribed for hypercholesterolemia and for prevention of cardiovascular diseases. [23] For the gene MIA3, with the sole SNP variant association of variants rs10495197 and rs17163303, it was found that each of the SNPs individually has the potential to influence the drug therapy for Vancomycin. [24] Vancomycin is the drug of choice for therapy of bacterial sepsis, meningitis, hemolytic anemia, and for reducing the levels of creatine kinase in blood.…”
Section: Pharmacogenetic Implication Studymentioning
confidence: 99%